2016
DOI: 10.1097/brs.0000000000001568
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lumbar Spine Sagittal Alignment and L4-L5 Disc Degeneration Among Asymptomatic Young Adults

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
4
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 20 publications
2
41
4
7
Order By: Relevance
“…In 2016, Rafael et al identified moderate associations between the spinopelvic parameters and disc degeneration in type II spine among asymptomatic people [9]. In our study, we only identified slightly negative correlations between the LL and disc degeneration grade at L4-L5 in groups B and C (Table 4).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In 2016, Rafael et al identified moderate associations between the spinopelvic parameters and disc degeneration in type II spine among asymptomatic people [9]. In our study, we only identified slightly negative correlations between the LL and disc degeneration grade at L4-L5 in groups B and C (Table 4).…”
Section: Discussionsupporting
confidence: 46%
“…Lumbar intervertebral disc degeneration (LDD), the main cause of lumbar spinal disorders, is associated with biomechanical stresses and increases with age [1][2][3][4][5][6]. Previous studies have demonstrated that sagittal spinopelvic alignment plays an important role in LDD [7][8][9]. Therefore, it is meaningful and useful to study the relationship between spinal sagittal morphology and disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical PI value was noted; whereby, a PI of 42 or lower exhibited a fourfold increased risk in the development of these phenotypes, this 42 was determined from ROC analyses. Several studies have investigated spinopelvic alignment in patients having certain signs of disc degeneration, 38 lumbar disc displacement, 39 and spondylolisthesis. 17 However, and in particular, excluding cases of spondylolisthesis and having a more robust definition of disc degeneration in our study, we noted the novel finding that PI was significantly related to MCs, UDS as well as lumbar disc displacement and the combination of the three phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to maintain proper upright posture be inferred that patients with a high L 4-5 I will show a high LL and correlate with our result. Consequently, with an increase in lordosis, there will be increased loading to the posterior complex of the lumbosacral spine, which can be a major cause of spondylolysis (5, 24,28,29,39). In addition, this may induce the development of spondylolisthesis because of a high L 4-5 S (5,7,8).…”
Section: Statisticsmentioning
confidence: 99%